A high performance stainless steel oxygen evolution electrode and its application
Through two-step electrolysis methods of pretreatment of stainless steel surface, anode corrosion and secondary electrolysis, high-performance stainless steel oxygen evolution electrodes were prepared, solving the problem of surface modification and high overpotential of stainless steel electrodes, and achieving low-cost and efficient hydro-hydrogen production effect.
Patent Information
- Application Number
- CN202410272865.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-11
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-03-11
AI Technical Summary
In the prior art, stainless steel needs surface modification when used for electrolytic water catalysis, and the overpotential is high, making it difficult to meet the demand for industrial alkaline electrolytic water.
High-performance stainless steel oxygen evolution electrodes were prepared by two-step electrolysis methods of pretreatment, anode corrosion and secondary electrolysis. The method includes performing anode corrosion in a chloride solution and performing structural reconstruction electrolysis in an alkali solution to improve the electronic characteristics and surface structure of the stainless steel electrode.
It greatly reduces the overpotential of the OER reaction, improves the conductivity, electrochemical active area and electrocatalytic properties of the electrode, so that it can show excellent comprehensive performance in electrolyzing hydrogen production, reduces production costs, and is easy to achieve industrial production.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of hydrogen production by electrolysis of water, and in particular to a high-performance stainless steel oxygen evolution electrode and application thereof. Background Art
[0002] Energy, as the core driving force of social and economic development, is facing severe challenges. With the increasing depletion of fossil fuels and the increasingly serious environmental problems, it has become a top priority to find a clean and sustainable energy source. Hydrogen energy, as a clean and efficient new energy source, is highly anticipated. However, to achieve large-scale application of hydrogen energy, it is necessary to solve the problem of how to prepare hydrogen efficiently and environmentally friendly. Water electrolysis, as a pure and pollution-free method of hydrogen production, is regarded as an ideal solution. The water decomposition reaction includes the hydrogen evolution reaction (HER) at the cathode and the oxygen evolution reaction (OER) at the anode.
[0003] However, the slow kinetics of the oxygen evolution reaction require a high overpotential for hydrogen production from water electrolysis, resulting in high energy consumption. OER catalysts with excellent performance can reduce the cost of hydrogen production from water electrolysis and improve the efficiency of hydrogen production from water electrolysis. Although precious metals such as IrO2 and RuO2 are currently the most effective OER catalysts, their high prices and scarcity limit the industrial application of hydrogen production technology from water electrolysis. Therefore, the design and development of non-precious metal catalysts is particularly important.
[0004] In recent years, the prior art has developed a variety of non-precious metal catalysts, such as transition metal oxides, sulfides, phosphides, borides, carbides, nitrides and their composites. These catalysts show certain catalytic activity under laboratory conditions, but they are easily affected by current shock or oxygen bubble evolution during electrolysis and fall off, resulting in reduced catalytic activity. In addition, the preparation process of these catalysts is complicated and costly, which is not conducive to industrial application. The use of stainless steel with excellent conductivity and low cost as an anode catalyst can not only reduce costs, but also eliminate the potential difference between the anode electrode and the bipolar plate, thereby improving the stability and service life of the alkaline electrolytic cell. However, when stainless steel is used directly as a catalyst, its catalytic performance is often not ideal, so it is necessary to carry out surface modification, such as oxidation, nitridation, sulfidation and phosphating, which not only increases the processing cost of stainless steel, but also has problems such as easy detachment of surface modification and complex modification process. The stainless steel catalyst prepared by the prior art using a one-step anodization method can be used at a high current density (570mA / cm 2 ) shows ultra-long stability. However, its high overpotential makes it difficult to meet the needs of industrial alkaline water electrolysis. Summary of the invention
[0005] In view of the above-mentioned deficiencies in the prior art, the purpose of the present invention is to provide a high-performance stainless steel oxygen evolution electrode and its application, so as to solve the problems in the prior art that stainless steel needs to be surface modified when used for water electrolysis catalysis, has a high overpotential, and is difficult to meet the needs of industrial alkaline water electrolysis.
[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0007] A high-performance stainless steel oxygen evolution electrode is prepared by the following steps:
[0008] Step 1: Pre-treat the stainless steel surface to remove impurities on its surface;
[0009] Step 2: placing the stainless steel treated in step 1 in a chloride solution, using a constant current density method, using the stainless steel as an anode for anodic corrosion for 2 to 5 minutes, then cleaning and drying the stainless steel to obtain an anodic corrosion stainless steel electrode; wherein the concentration of chloride in the chloride solution is 3 to 5 wt%, and the current density during anodic corrosion is 300 to 500 mA / cm 2 ;
[0010] Step 3: placing the stainless steel electrode treated in step 2 in an alkaline solution, and electrolyzing the stainless steel as an anode to obtain the stainless steel oxygen evolution electrode; wherein the concentration of the alkali in the alkaline solution is 1-2 mol / L, and the current density during electrolysis is 400-600 mA / cm 2 , the electrolysis time is 1 to 3 hours.
[0011] Preferably, calculated by weight percentage, the Cr content in the stainless steel is greater than 5%, and the Ni content is greater than 5%.
[0012] Calculated by weight percentage, the stainless steel includes the following components: 16-18% Cr, 10-14% Ni, 2-3% Si, 0-2% Mn, and the balance is Fe.
[0013] Preferably, in step 1, the stainless steel is pickled with dilute sulfuric acid, the concentration of the dilute sulfuric acid is 1 to 2 mol / L, and the pickling time is 10 to 20 min.
[0014] Preferably, in step 2, the chloride includes one of NaCl and KCl or a mixture of the two.
[0015] Preferably, in step 3, the base is KOH, NaOH or a mixture of the two.
[0016] The present invention also provides an application of a high-performance stainless steel oxygen evolution electrode, wherein the high-performance stainless steel oxygen evolution electrode is used for electrolyzing water to evolve oxygen.
[0017] Preferably, the stainless steel oxygen evolution electrode acts as an anode to evolve oxygen during water electrolysis.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] 1. The stainless steel oxygen evolution electrode of the present invention is prepared by two-step electrolysis of stainless steel. By coupling the two-step electrolysis method of anode corrosion and structural reconstruction, the electronic properties and surface structure of the stainless steel electrode are first improved, and then the specific surface area and porosity of the stainless steel electrode are further increased by structural reconstruction, while the conductivity of the electrons is improved, and finally the OER reaction mechanism of the stainless steel electrode is induced to change from AEM to LOM with higher catalytic activity, which greatly reduces the OER reaction overpotential. These improvements give the stainless steel oxygen evolution electrode better conductivity, enhance the electrochemical active area and electrocatalytic performance, so that it exhibits excellent comprehensive performance in the process of electrolysis of water to produce hydrogen.
[0020] 2. The preparation method of the stainless steel oxygen evolution electrode of the present invention has a simple process, mild reaction conditions, high production efficiency, easy control of the entire reaction process, and low energy consumption, which greatly reduces the production cost and is easy to realize industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a scanning electron microscope photo of stainless steel without any treatment;
[0022] Figure 2 This is a scanning electron microscope photograph of the stainless steel oxygen evolution electrode obtained in Comparative Example 1 of the present invention;
[0023] Figure 3 This is a scanning electron microscope photo of the enlarged pit-like structure on the surface of the stainless steel oxygen evolution electrode obtained in Comparative Example 1 of the present invention;
[0024] Figure 4 This is a scanning electron microscope photograph of the stainless steel oxygen evolution electrode obtained in Comparative Example 2 of the present invention;
[0025] Figure 5 This is a scanning electron microscope photograph of the stainless oxygen evolution electrode obtained in Example 1 of the present invention;
[0026] Figure 6 LSV curves of the stainless steel oxygen evolution electrodes obtained in Comparative Example 1, Comparative Example 2, Example 1 of the present invention and the stainless steel without any treatment;
[0027] Figure 7 The electrochemical impedance spectra of the stainless steel oxygen evolution electrodes obtained in Comparative Example 1, Comparative Example 2, and Example 1 of the present invention and the stainless steel without any treatment;
[0028] Figure 8The electrochemical specific surface area diagram of the stainless steel oxygen evolution electrode obtained in Comparative Example 1, Comparative Example 2, Example 1 of the present invention and the stainless steel without any treatment;
[0029] Fig. 9 The Raman test results of the stainless steel oxygen evolution electrodes obtained in Comparative Example 1, Comparative Example 2 and Example 1 of the present invention after oxygen evolution reaction in TMAOH solution;
[0030] Fig.10 The in-situ electrochemical differential mass spectrometry experimental results of the stainless steel oxygen evolution electrode obtained in Example 1 of the present invention;
[0031] Fig.11 Schematic diagram of the reaction steps of AEM and LOM mechanisms.
[0032] In the figure: SS-AC is comparative example 1; SS-SR is comparative example 2; SS-AC-SR is embodiment 1; SS-control sample. DETAILED DESCRIPTION
[0033] The present invention will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. All other embodiments obtained by ordinary technicians in this field based on the present invention belong to the scope of protection of the present invention.
[0034] Unless otherwise indicated in specific cases in the present invention, the numerical ranges listed herein include the upper and lower limits, and all integers and fractions within the range, and are not limited to the specific values listed when defining the range.
[0035] 1. A high performance stainless steel oxygen evolution electrode
[0036] The electrode of the present invention is prepared by the following steps:
[0037] Step 1: Pre-treat the stainless steel surface to remove impurities on its surface;
[0038] Step 2: placing the stainless steel treated in step 1 in a chloride solution, using a constant current density method, using the stainless steel as an anode for anodic corrosion for 2 to 5 minutes, then cleaning and drying the stainless steel to obtain an anodic corrosion stainless steel electrode; wherein the concentration of chloride in the chloride solution is 3 to 5 wt%, and the current density during anodic corrosion is 300 to 500 mA / cm 2 ;
[0039] Step 3: placing the stainless steel electrode treated in step 2 in an alkaline solution, and electrolyzing the stainless steel as an anode to obtain the stainless steel oxygen evolution electrode; wherein the concentration of the alkali in the alkaline solution is 1-2 mol / L, and the current density during electrolysis is 400-600 mA / cm 2 , the electrolysis time is 1 to 3 hours.
[0040] When studying the use of stainless steel as an electrode for electrolyzing water, the present invention found that after the stainless steel was subjected to anodic corrosion, the metal on the surface of the stainless steel was oxidized, and multi-component metal oxides / hydroxides with OER catalytic activity were generated in situ on the surface of the stainless steel, among which the key active substance Ni-Fe LDH was formed. When the anodic-corroded stainless steel was placed in an alkaline solution for further electrolysis, it was found that the electrolysis in this process would cause the surface structure of the stainless steel to be reconstructed, and some metal oxides would be transformed into metal hydroxides. At the same time, the number of oxygen defects on the surface of the stainless steel increased, and the inactive element Cr was selectively dissolved, thereby increasing the proportion of nickel and iron on the surface of the stainless steel. This series of transformations began to induce the original OER reaction mechanism of the stainless steel oxygen evolution electrode to change from the adsorbate evolution mechanism (AEM) to the lattice oxygen evolution mechanism (LOM) with higher catalytic activity during the electrolysis of water. Fig.11 Schematic diagram of the reaction steps of the AEM and LOM mechanisms. Such evolution greatly reduces the overpotential of the OER reaction. After in-depth research on the surface of this stainless steel oxygen evolution electrode, the present invention found that the method of the present invention improves the electronic properties and surface structure of the stainless steel surface, increases its specific surface area and porosity, and also improves the conduction efficiency of electrons. These improvements give the stainless steel electrode better conductivity, enhanced electrochemical active area and electrocatalytic performance, so that it exhibits excellent comprehensive performance in the electrolysis of water to produce hydrogen.
[0041] In some embodiments, when anodic corrosion is performed in step 2, a two-electrode system can be used, with a stainless steel sheet as the anode and a graphite rod as the cathode. The method of the present invention is essentially different from electrodeposition. In the present invention, the stainless steel at the anode loses electrons and is oxidized and corroded under the action of voltage, while electrodeposition refers to the process of depositing cations in the solution onto the cathode under the action of voltage. The concentration of chloride in the chloride solution is controlled between 3 and 5wt%, preferably 4wt%, for example, 3wt%, 4wt%, 5wt%, etc., and all ranges and sub-ranges between the above values. When the chloride concentration is low, the current transfer efficiency is low. When the chloride concentration is high, the anode will produce a chlorine evolution reaction, which will reduce the oxygen evolution performance of the electrode. The current density is controlled at 300 to 500mA / cm during anode corrosion. 2 , preferably 400mA / cm 2 , for example, 300 mA / cm 2 , 400mA / cm 2, 500mA / cm 2 Etc., and all ranges and sub-ranges between the above values. When the current density is small, the oxidation rate is slow and the corrosion efficiency is reduced. When the current density is large, the electrode surface will be excessively corroded, which will reduce the oxygen evolution performance of the electrode. The anode corrosion time is controlled between 2 and 5 minutes, preferably 3 minutes, for example, 2 minutes, 3 minutes, 4 minutes, 5 minutes, etc., and all ranges and sub-ranges between the above values. When the anode corrosion time is small, it is impossible to form enough OER active substances on the electrode surface. When the anode corrosion time is too long, the electrode surface will be excessively corroded, which will reduce the oxygen evolution performance of the electrode. It should be understood that in the embodiment, any of the above ranges can be combined with any other ranges in other embodiments.
[0042] In some embodiments, step 3 performs secondary electrolysis to further restructure the stainless steel surface after anodic corrosion. A two-electrode system can be used, with the anodic corrosion stainless steel electrode as the anode, the graphite rod as the cathode, and the electrolyte as an alkaline solution. Among them, the concentration of the alkaline solution is controlled between 1 and 2 mol / L, which can be 1 mol / L, 2 mol / L, etc., and all ranges and sub-ranges between the above values. When the alkali concentration is small, the current transfer efficiency is low. When the alkali concentration is large, the solution viscosity increases and the conductivity decreases, which will reduce the oxygen evolution performance of the electrode. The current density during electrolysis is controlled at 400-600mA / cm 2 Between, can be 400mA / cm 2 , 500mA / cm 2 、600mA / cm 2 Etc., and all ranges and sub-ranges between the above values. When the current density is small, the oxidation rate is slow, and it is difficult for the electrode surface to undergo structural reconstruction. When the current density is large, the electrode surface will be excessively corroded, which will reduce the oxygen evolution performance of the electrode. The electrolysis time is controlled between 1 and 3 hours, which can be 1 hour, 2 hours, 3 hours, etc., and all ranges and sub-ranges between the above values. When the structural reconstruction time is small, the inactive substance Cr cannot be fully dissolved, the oxide on the electrode surface cannot be fully converted into hydroxide, the oxygen defect concentration cannot be increased, and the OER reaction mechanism of the stainless steel electrode cannot be induced to change, which will reduce the oxygen evolution performance of the electrode. When the structural reconstruction time is too long, the energy consumption of the entire preparation process will be unnecessarily increased, thereby increasing the preparation cost. It should be understood that in the embodiment, any of the above ranges can be combined with any other ranges in other embodiments.
[0043] In some embodiments, the Cr content in the stainless steel is greater than 5%, and the Ni content is greater than 5%, calculated by weight percentage. This method is applicable to almost all stainless steels with a mass fraction of Cr and Ni greater than 5%. When the Ni content in the stainless steel is low, the key OER active substance Ni cannot be formed on the electrode surface. x Fe 1-x OOH. When the Cr content in stainless steel is low, the inactive element Cr will not be dissolved in the second step of electrolysis, and the ratio of Ni and Fe will not change, which may not induce changes in the OER reaction mechanism of the stainless steel electrode. In the embodiment, the stainless steel described in the present invention is 316L stainless steel, calculated by weight percentage, including the following components: 16-18% Cr, 10-14% Ni, 2-3% Si, 0-2% Mn, and the balance is Fe.
[0044] In some embodiments, in step 1, the stainless steel is pickled with dilute sulfuric acid. The role of dilute sulfuric acid is to remove rust and impurities on the surface of the stainless steel to prevent it from affecting the effect of subsequent anodic corrosion. Therefore, the concentration of dilute sulfuric acid is not easy to be too high. Too high will cause the stainless steel to be excessively corroded, and then the anodic corrosion will have an adverse effect; the concentration is not easy to be too low, and too low will not have a cleaning effect. Therefore, the concentration of dilute sulfuric acid can be 1mol / L, 1.5mol / L, 2mol / L, etc., and all ranges and sub-ranges between the above values. The pickling time can be controlled at 10min, 15min, 20min, etc., and all ranges and sub-ranges between the above values. It should be understood that in the embodiment, any of the above ranges can be combined with any other ranges in other embodiments.
[0045] In some embodiments, in step 2, the chloride includes one of NaCl and KCl, or a mixture of the two.
[0046] In some embodiments, in step 3, the base includes KOH, NaOH, or a mixture of the two.
[0047] The present invention also provides an application of a high-performance stainless steel oxygen evolution electrode, which is used for electrolyzing water to evolve oxygen. In a specific implementation, the stainless steel oxygen evolution electrode acts as an anode to evolve oxygen during the electrolysis of water.
[0048] 2. Examples and Comparative Examples
[0049] Example 1
[0050] Step 1: Pretreatment of stainless steel materials:
[0051] Take 316L foam stainless steel, cut it into rectangles, polish the stainless steel surface with 500-grit sandpaper for 5 minutes, then soak it in 1 mol / L dilute sulfuric acid solution for 20 minutes, slowly rinse it with deionized water for 3 minutes and dry it for 6 hours to obtain a rectangular stainless steel sheet.
[0052] Step 2: Preparation of stainless steel electrode for anodic corrosion:
[0053] A two-electrode system is used, with a rectangular stainless steel sheet as the anode, a graphite rod as the cathode, and a NaCl solution as the electrolyte. The treated rectangular stainless steel sheet is placed in the NaCl solution for anodic corrosion for 4 minutes to obtain an anodic corrosion stainless steel electrode. The current density during anodic corrosion is 400 mA / cm 2 , the electrolyte concentration during anode corrosion is 4wt%.
[0054] Step 3: Preparation of stainless steel electrodes for structural reconstruction:
[0055] A two-electrode system was used, with an anodic corrosion stainless steel electrode as the anode, a graphite rod as the cathode, and a KOH solution as the electrolyte. The anodic corrosion stainless steel electrode was placed in a KOH solution for secondary electrolysis for 2 hours to obtain the final stainless steel oxygen evolution electrode. The current density during structural reconstruction was 500 mA / cm 2 The electrolyte concentration during structural reconstruction was 1 mol / L.
[0056] Example 2
[0057] The improvement is made on the basis of Example 1, and the difference is that in step 2, the current density of the anode corrosion is 300 mA / cm 2 .
[0058] Example 3
[0059] The improvement is made on the basis of Example 1, and the difference is that in step 2, the current density of the anode corrosion is 500 mA / cm 2 .
[0060] Example 4
[0061] An improvement is made on the basis of Example 1, which differs therefrom in that: in step 2, the NaCl concentration is 3 wt %.
[0062] Example 5
[0063] An improvement is made on the basis of Example 1, which differs therefrom in that: in step 2, the NaCl concentration is 5 wt %.
[0064] Example 6
[0065] An improvement is made on the basis of Example 1, and the difference therefrom is that in step 3, the KOH concentration is 2 mol / L.
[0066] Example 7
[0067] The improvement is made on the basis of Example 1, and the difference is that in step 3, the current density is 400 mA / cm 2 .
[0068] Example 8
[0069] The improvement is made on the basis of Example 1, and the difference is that in step 3, the current density is 600 mA / cm 2 .
[0070] Example 9
[0071] An improvement is made on the basis of Example 1, and the difference therefrom is that in step 3, the electrolysis time is 1 hour.
[0072] Example 10
[0073] An improvement is made on the basis of Example 1, and the difference therefrom is that in step 3, the electrolysis time is 3 hours.
[0074] Embodiment 11
[0075] An improvement is made on the basis of Example 1, and the difference therefrom is that in step 1, the material is 304 stainless steel mesh.
[0076] Comparative Example 1
[0077] Step 1: Pretreatment of stainless steel materials:
[0078] Take 316L foam stainless steel, cut it into rectangles, polish the stainless steel surface with 500-grit sandpaper for 5 minutes, then soak it in 1 mol / L dilute sulfuric acid solution for 20 minutes, slowly rinse it with deionized water for 3 minutes and dry it for 6 hours to obtain a rectangular stainless steel sheet.
[0079] Step 2: Preparation of stainless steel electrode for anodic corrosion:
[0080] The treated rectangular stainless steel sheet was placed in a NaCl solution for anodic corrosion for 2 minutes to obtain an anodic corrosion stainless steel electrode. The current density during anodic corrosion was 400 mA / cm 2 , the electrolyte concentration during anode corrosion is 4wt%.
[0081] Comparative Example 2
[0082] Step 1: Pretreatment of stainless steel materials:
[0083] Take 316L foam stainless steel, cut the 316L foam stainless steel into a rectangle, polish the stainless steel surface with 500-mesh sandpaper for 5 minutes, then soak it in 1 mol / L dilute sulfuric acid solution for 20 minutes, slowly rinse it with deionized water for 3 minutes and dry it for 6 hours to obtain a rectangular stainless steel sheet.
[0084] Step 2: Preparation of stainless steel electrodes for structural reconstruction:
[0085] The anode-corroded stainless steel electrode was placed in a KOH solution for electrolysis for 2 hours to obtain the final stainless steel oxygen evolution electrode. The current density during structural reconstruction was 500 mA / cm 2 The electrolyte concentration during structural reconstruction was 1 mol / L.
[0086] Comparative Example 3
[0087] Step 1: Pretreatment of stainless steel materials:
[0088] Take 316L foam stainless steel, cut it into rectangles, polish the stainless steel surface with 500-grit sandpaper for 5 minutes, then soak it in 1 mol / L dilute sulfuric acid solution for 20 minutes, slowly rinse it with deionized water for 3 minutes and dry it for 6 hours to obtain a rectangular stainless steel sheet.
[0089] Step 2: Preparation of stainless steel electrode for anodic corrosion:
[0090] A two-electrode system is used, with a rectangular stainless steel sheet as the anode, a graphite rod as the cathode, and a NaCl solution as the electrolyte. The treated rectangular stainless steel sheet is placed in the NaCl solution for anodic corrosion for 4 minutes to obtain an anodic corrosion stainless steel electrode. The current density during anodic corrosion is 400 mA / cm 2 , the electrolyte concentration during anode corrosion is 1wt%.
[0091] Step 3: Preparation of stainless steel electrodes for structural reconstruction:
[0092] A two-electrode system was used, with an anodic corrosion stainless steel electrode as the anode, a graphite rod as the cathode, and a KOH solution as the electrolyte. The anodic corrosion stainless steel electrode was placed in a KOH solution for secondary electrolysis for 2 hours to obtain the final stainless steel oxygen evolution electrode. The current density during structural reconstruction was 500 mA / cm 2 The electrolyte concentration during structural reconstruction was 1 mol / L.
[0093] Comparative Example 4
[0094] Step 1: Pretreatment of stainless steel materials:
[0095] Take 316L foam stainless steel, cut it into rectangles, polish the stainless steel surface with 500-grit sandpaper for 5 minutes, then soak it in 1 mol / L dilute sulfuric acid solution for 20 minutes, slowly rinse it with deionized water for 3 minutes and dry it for 6 hours to obtain a rectangular stainless steel sheet.
[0096] Step 2: Preparation of stainless steel electrode for anodic corrosion:
[0097] A two-electrode system is used, with a rectangular stainless steel sheet as the anode, a graphite rod as the cathode, and a NaCl solution as the electrolyte. The treated rectangular stainless steel sheet is placed in the NaCl solution for anodic corrosion for 4 minutes to obtain an anodic corrosion stainless steel electrode. The current density during anodic corrosion is 400 mA / cm 2 The electrolyte concentration during anode corrosion is 6wt%.
[0098] Step 3: Preparation of stainless steel electrodes for structural reconstruction:
[0099] A two-electrode system was used, with an anodic corrosion stainless steel electrode as the anode, a graphite rod as the cathode, and a KOH solution as the electrolyte. The anodic corrosion stainless steel electrode was placed in a KOH solution for secondary electrolysis for 2 hours to obtain the final stainless steel oxygen evolution electrode. The current density during structural reconstruction was 500 mA / cm 2 The electrolyte concentration during structural reconstruction was 1 mol / L.
[0100] Comparative Example 5
[0101] Step 1: Pretreatment of stainless steel materials:
[0102] Take 316L foam stainless steel, cut it into rectangles, polish the stainless steel surface with 500-grit sandpaper for 5 minutes, then soak it in 1 mol / L dilute sulfuric acid solution for 20 minutes, slowly rinse it with deionized water for 3 minutes and dry it for 6 hours to obtain a rectangular stainless steel sheet.
[0103] Step 2: Preparation of stainless steel electrode for anodic corrosion:
[0104] A two-electrode system was used, with a rectangular stainless steel sheet as the anode, a graphite rod as the cathode, and a NaCl solution as the electrolyte. The treated rectangular stainless steel sheet was placed in the NaCl solution for anodic corrosion for 4 minutes to obtain an anodic corrosion stainless steel electrode. The current density during anodic corrosion was 200 mA / cm 2 , the electrolyte concentration during anode corrosion is 4wt%.
[0105] Step 3: Preparation of stainless steel electrodes for structural reconstruction:
[0106] A two-electrode system was used, with an anodic corrosion stainless steel electrode as the anode, a graphite rod as the cathode, and a KOH solution as the electrolyte. The anodic corrosion stainless steel electrode was placed in a KOH solution for secondary electrolysis for 2 hours to obtain the final stainless steel oxygen evolution electrode. The current density during structural reconstruction was 500 mA / cm 2 The electrolyte concentration during structural reconstruction was 1 mol / L.
[0107] Comparative Example 6
[0108] Step 1: Pretreatment of stainless steel materials:
[0109] Take 316L foam stainless steel, cut it into rectangles, polish the stainless steel surface with 500-grit sandpaper for 5 minutes, then soak it in 1 mol / L dilute sulfuric acid solution for 20 minutes, slowly rinse it with deionized water for 3 minutes and dry it for 6 hours to obtain a rectangular stainless steel sheet.
[0110] Step 2: Preparation of stainless steel electrode for anodic corrosion:
[0111] A two-electrode system was used, with a rectangular stainless steel sheet as the anode, a graphite rod as the cathode, and a NaCl solution as the electrolyte. The treated rectangular stainless steel sheet was placed in the NaCl solution for anodic corrosion for 4 minutes to obtain an anodic corrosion stainless steel electrode. The current density during anodic corrosion was 700 mA / cm 2 , the electrolyte concentration during anode corrosion is 4wt%.
[0112] Step 3: Preparation of stainless steel electrodes for structural reconstruction:
[0113] A two-electrode system was used, with an anodic corrosion stainless steel electrode as the anode, a graphite rod as the cathode, and a KOH solution as the electrolyte. The anodic corrosion stainless steel electrode was placed in a KOH solution for secondary electrolysis for 2 hours to obtain the final stainless steel oxygen evolution electrode. The current density during structural reconstruction was 500 mA / cm 2 The electrolyte concentration during structural reconstruction was 1 mol / L.
[0114] 3. Performance Analysis
[0115] 1. Microscopic morphology
[0116] The examples and comparative examples as well as the stainless steel (control sample) not subjected to any treatment were placed on a JSM-7800F scanning electron microscope produced by JEOL Ltd. (JEOL) for microscopic morphology observation.
[0117] Depend on Figure 1 and Figure 2It can be seen that compared with the stainless steel without any treatment, the specific surface area of the surface of the stainless steel oxygen evolution electrode obtained in Comparative Example 1 is improved, and its scanning electron microscope photo shows many pit-like structures; the specific surface area of the surface of the stainless steel electrode obtained in Comparative Example 2 is obviously not as good as that in Comparative Example 1, and only some gully-like structures are formed; Taking Example 1 as an example, the specific surface area of the surface of the stainless steel electrode prepared in Example 1 is significantly greater than that of Comparative Example 1 and Comparative Example 2, Figure 5 It can be seen that the surface of the stainless steel electrode prepared in the embodiment of the present invention has both a pit-like structure and a gully structure, which can further increase the contact area between the stainless steel oxygen evolution electrode and the electrolyte and accelerate the release of bubbles. The same microscopic morphology as in Example 1 can also be observed on the surface of the stainless steel electrode prepared in other embodiments of the present invention.
[0118] 2. Determination of overpotential
[0119] The embodiments and comparative examples, as well as stainless steel (control sample) without any treatment, were placed on a CHI1140C electrochemical workstation produced by Shanghai Chenhua Instrument Co., Ltd. to measure the LSV curve. The oxygen evolution performance test was carried out using a three-electrode system, with a stainless steel electrode as the anode, a graphite rod as the cathode, Hg / HgO as the reference electrode, and a 1 mol / L KOH solution as the electrolyte. This method is different from the second step electrolysis.
[0120] Table 1 Overpotential measurement results of different stainless steel-based electrodes
[0121]
[0122] Depend on Figure 6 As can be seen from Table 1, the overpotential of the embodiment of the present invention has been greatly reduced, which is obviously lower than the overpotential of the comparative example and the control sample. Even under the condition of higher current density, the overpotential of the electrode prepared by the embodiment of the present invention is still relatively low. The overpotentials of Comparative Examples 1 and 2, which only perform anode corrosion or structural reconstruction, are higher than those of the embodiment; Comparative Examples 3 and 4 adjust the electrolyte concentration during anode corrosion, and it can be seen that the overpotential is even higher than that of Comparative Examples 1 and 2; Comparative Examples 5 and 6 adjust the current density during anode corrosion, and the same situation as Comparative Examples 3 and 4 occurs. This shows that the electrolyte concentration and current density during anode corrosion will affect the overpotential of the stainless steel oxygen evolution electrode, and it also shows that the stainless steel oxygen evolution electrode obtained by the present invention also has excellent catalytic performance. Therefore, the stainless steel oxygen evolution electrode obtained by the present invention is expected to be applied to the industrial electrolysis of water to produce hydrogen industry.
[0123] 3. Electrochemical impedance spectroscopy
[0124] The examples and comparative examples, as well as stainless steel without any treatment (control sample), were placed on a CHI1140C electrochemical workstation produced by Shanghai Chenhua Instrument Co., Ltd. to measure electrochemical impedance spectroscopy (EIS).
[0125] Table 2 Electrochemical impedance spectroscopy results of different stainless steel-based electrodes
[0126]
[0127]
[0128] Depend on Figure 7 As can be seen from Table 2, the Nyquist plots obtained from the electrochemical impedance spectroscopy test of the stainless steel oxygen evolution electrode prepared in the embodiments of the present invention and the comparative examples and the stainless steel without any treatment are all approximately semicircular. Since the smaller the radius of the semicircle of the Nyquist plot (i.e., the impedance plot), the lower the impedance of the material; therefore, the electrode impedance prepared in Comparative Example 1 is the smallest, followed by the electrode prepared in the embodiment, and the electrode impedance prepared in Comparative Example 2 is higher, but compared with the control sample, the electrode impedances prepared in the embodiment and the comparative example have been significantly reduced. This also shows that anodic corrosion can significantly reduce the impedance of the electrode. Although secondary electrolysis will lead to an increase in impedance, considering the contribution to the reduction of overpotential, the electrode prepared in the embodiment still has good conductivity. At the same time, it can be seen from Comparative Examples 3 to 6 that the concentration of the electrolyte and the current density during anodic corrosion will lead to an increase in the electrochemical impedance of the electrode, and this increase is even greater than that of Comparative Examples 1 and 2.
[0129] 4. Determination of electrochemical specific surface area
[0130] The examples and comparative examples, as well as stainless steel (control sample) without any treatment, were placed on a CHI1140C electrochemical workstation produced by Shanghai Chenhua Instrument Co., Ltd. to measure cyclic voltammetry curves (CV curves). The electrochemical specific surface area (C dl ).
[0131] Table 3 Electrochemical specific surface area determination results of different stainless steel-based electrodes
[0132]
[0133]
[0134] Figure 8 is the cyclic voltammetry curve of each sample. By fitting the cyclic voltammetry curve of each sample, the electrochemical specific surface area (C dl ),like Fig. 9 As shown. Fig. 9As can be seen from Table 3, both Comparative Examples 1 and 2 only performed one step of the method of the present invention, and such treatment had a very limited effect on the improvement of the electrochemical specific surface area. However, the embodiment of the present invention greatly improved the electrochemical specific surface area of the electrode through the structural reorganization of anode corrosion and secondary electrolysis, and increased the electrochemical specific surface area to 15.5 mF·cm -2 In Comparative Example 3, due to insufficient electrolyte concentration during anode corrosion, insufficient anode corrosion occurred on the electrode surface. Even after structural reconstruction, the improvement in electrochemical specific surface area was not as good as that in Comparative Example 1. Although the electrochemical specific surface area of Comparative Example 3 was greatly improved, other properties of the comparative example declined, and the comprehensive performance was far inferior to that of the embodiment. Comparative Example 5 shows that insufficient current density during anode corrosion will make insufficient contribution to the improvement of the electrochemical specific surface area of the electrode, and Comparative Example 6 also proves that excessive anode corrosion current density will reduce the beneficial effect of anode corrosion on the improvement of the electrochemical specific surface area of the electrode.
[0135] 5. Evolution of catalytic mechanisms
[0136] Fig. 9 The Raman test results of Comparative Example 1, Comparative Example 2 and Example 1 show that TMA is only observed in the Raman spectrum of Example 1. + This is due to the O generated in the LOM reaction mechanism. 2- With TMA + There is a specific binding effect between them, which indicates that the OER reaction mechanism of Comparative Examples 1 and 2 is AEM, while the OER reaction mechanism of Example 1 is LOM, which proves that the reaction mechanism of the electrode has changed after treatment by the method of the present invention. Fig.10 The in-situ electrochemical differential mass spectrometry experimental results of the stainless steel oxygen evolution electrode obtained in Example 1 directly show that after the 316L foam stainless steel undergoes anodic corrosion and structural reconstruction, the OER reaction mechanism of the stainless steel oxygen evolution electrode is a lattice oxygen evolution mechanism (LOM) with higher catalytic activity.
[0137] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the technical solution. Those skilled in the art should understand that those modifications or equivalent substitutions of the technical solution of the present invention that do not depart from the purpose and scope of the technical solution should be included in the scope of the claims of the present invention.
Claims
1. A high performance stainless steel oxygen evolution electrode, characterized in that: The electrode is prepared by the following steps: Step 1: Pre-treat the stainless steel surface to remove impurities on its surface; Step 2: placing the stainless steel treated in step 1 in a chloride solution, using a constant current density method, using the stainless steel as an anode for anodic corrosion for 2 to 5 minutes, then cleaning and drying the stainless steel to obtain an anodic corrosion stainless steel electrode; wherein the concentration of chloride in the chloride solution is 3 to 5 wt%, and the current density during anodic corrosion is 300 to 500 mA / cm 2 ; Step 3: placing the stainless steel electrode treated in step 2 in an alkaline solution, and electrolyzing the stainless steel as an anode to obtain the stainless steel oxygen evolution electrode; wherein the concentration of the alkali in the alkaline solution is 1-2 mol / L, and the current density during electrolysis is 400-600 mA / cm 2 , electrolysis time is 1~3h; Calculated by weight percentage, the Cr content in the stainless steel is greater than 5%, and the Ni content is greater than 5%.
2. The high performance stainless steel oxygen evolution electrode according to claim 1, characterized in that: Calculated by weight percentage, the stainless steel includes the following components: 16-18% Cr, 10-14% Ni, 2-3% Si, 0-2% Mn, and the balance is Fe.
3. The high performance stainless steel oxygen evolution electrode according to claim 1, characterized in that: In step 1, the stainless steel is pickled with dilute sulfuric acid, the concentration of the dilute sulfuric acid is 1-2 mol / L, and the pickling time is 10-20 min.
4. The high performance stainless steel oxygen evolution electrode according to claim 1, characterized in that: In step 2, the chloride includes one of NaCl and KCl or a mixture of the two.
5. The high performance stainless steel oxygen evolution electrode according to claim 1, characterized in that: In step 3, the base is one or both of KOH and NaOH.
6. Application of a high-performance stainless steel oxygen evolution electrode, characterized in that: The high-performance stainless steel oxygen evolution electrode described in any of claims 1 to 5 is used for electrolyzing water to evolve oxygen.
7. The use of the high performance stainless steel oxygen evolution electrode according to claim 6, characterized in that: The stainless steel oxygen evolution electrode acts as an anode to evolve oxygen during the water electrolysis process.
Citation Information
Patent Citations
Method for preparing high-activity oxygen evolution electrode material by electrochemical induction
CN110791772A
Stainless steel-based catalyst as well as preparation method and application thereof
CN113481530A